E-Servicescape and Perceived Green Value: Shaping Digital Consumer Behavior in the Sustainable Tourism Sector -An Empirical Study of a Sample of Users of the Al-Aurasi Hotel Website- - Hammad, Sabiha; El Amine , Belayachi Mohammed (Journal of Ecohumanism, 2026)
This study examines how the e‑servicescape of hotel websites and perceived green value shape digital consumer behavior in the sustainable tourism sector, focusing on users of the El‑Aurassi Hotel website. It adopts a quantitative descriptive–analytical approach and collects data through an online questionnaire administered to website users. The e‑servicescape is conceptualized through key dimensions such as aesthetic appeal, usability, interactivity, and green‑oriented personalization, while perceived green value reflects users’ assessment of the hotel’s environmental commitment and the added ecological benefit of choosing its services.The findings show that respondents hold generally positive perceptions of the website’s e‑servicescape, especially regarding usability and clarity of information. Results also indicate a positive and statistically significant effect of the e‑servicescape on perceived green value, which in turn supports more favorable digital consumer behaviors, such as intention to book, preference for the hotel, and willingness to engage in positive electronic word‑of‑mouth. The study concludes that a well‑designed, user‑friendly, and environmentally communicative website can serve as a strategic lever to enhance perceived green value and promote more sustainable tourism choices online, and it offers theoretical and practical recommendations for designing sustainability‑oriented e‑servicescapes.